Analysis of the New Medical Emergency for the Timely Detection and Integral Care of Child and Adolescent Cancer - Bazán Dobbertin, Ursula (2020)
This article analyzes the text the Law of Medical Emergency for the Timely Detection and Comprehensive Care of Child Cancer, approved by the Congress of the Republic on July 31, 2020 and published on September 2 of the same year. Although this law constitutes a necessary contribution to provide protection to the child and adolescent population diagnosed with cancer, it would have been opportune to contemplate various principles of protection for family members.